The mechanisms of distortion between ages and courses in Brazil: an ethnic and social divide, and a challenge for education policy - Rambla, Xavier; Saldanha Pereira, Rosangela; Gallego, Liliana María (Education Policy Analysis Archives, 2013)
The article contextualises over-age enrolment within the social divisions affecting the education system in Brazil. The following section analyses to what extent the components of multidimensional poverty impinge on the probability for a student to attend a course corresponding to a lower age. This analysis is helpful to discuss two mechanisms that provoke educational inequalities according to the international specialists. These are the accumulation of accumulation of material, social and cultural deprivation along people’s life, and opportunity hoarding through social closure. Both of them contribute significantly to over-age enrolment in Brazil.